Acid-catalysed reactions of bio-oil in liquid phase - Wu, Liping (Curtin University, 2016)
Under acid-catalysed condition, the behaviour of different components in bio-oil with alcohols or water was investigated. Heavy carboxylic acids and phenolics in bio-oil were quantified. The reaction routes of typical components including carboxylic acids and phenolics were distinctly different in alcohols and water. The coke formation during this process varied with different experimental parameters. Two types of acid catalysts, mineral acid and solid acid, had different effects on the acid-treatment of bio-oil.